Isolation and characterization of rabbit bone marrow-derived mesenchymal stem cells - Abofila, Marwan T. M.; Azab, Azab Elsayed; U. M, Imam; Ng, M. H.; R, Ramasamy; H. C, Chen; S, Ganabadi (Auctores Publishing, 2021)
Background: Stem cells are defined as cells that can self-renew indefinitely and able to differentiate into various mature cells when induced appropriately. It have many other properties bring attention to use in regenerative medicine. Stem cell therapy has attracted much interest in this 21st century, not only because of the controversy surrounding the ethics involving pluripotent stem cells, but their potential for clinical use. Objectives: The aim of this study was to isolate and characterize mesenchymal stem cells from bone marrow of New Zealand white rabbits by its morphological, multipotential differentiation an immunophenotypical analysis. Materials and Methods: Three rabbits were euthanized with pentobarbital, an incision was made through the skin at thigh region and all muscles related to femoral bone were removed. The two epiphysis ends were cut ant the bone marrow was flushed to be cultured for series of passages. Results: The bone marrow cells were shown to adhere to the plastic surface and started to form fibroblastic-like colonies after 3 to 7 days of initial seeding. Further characterization was conducted using cells from passage two onward by analyzing their surface protein expression and ability to differentiate into mesodermal lineages under a relevant inductive condition. Flow cytometer analysis showed that the adherent bone marrow cells were expressing CD44 and CD90 but not CD34 which is a standard profile of mesenchymal stem cells. Besides, the bone marrow cells which were subjected to adipogenic and osteogenic differentiation exhibited differentiation into adipocytes and osteoblasts when cultured in appropriate inductive differentiation media. Conclusion: Based on our observation, the bone marrow adherent cells from New Zealand white rabbits had reflected common mesenchymal stem cells characteristics which have been confirmed via morphological, multipotential ability and immunophenotyping analysis.